The Microbial Landscape in Patients with Cystic Lesion of Paranasal Sinuses - Xayitov AA (Genius Journals, 2024)
The problem of timely diagnosis of chronic cystic sinusitis and the choice of the necessary treatment remains relevant in modern Otorhinolaryngology. Timely diagnosis and treatment of cystic processes of the paranasal sinuses of the nose is one of the priorities of Otorhinolaryngology due to the increased incidence of this pathology. The main factor in the pathogenesis of the development of sinusitis is characteristic not only of the anatomical features of the structure of the nasal cavity, but also of the bacterial factor, which is sometimes represented by various types of microorganisms. The purpose of the study was to study the microbial landscape spectrum of sinuses in patients with chronic sinusitis. The study involved 157 people diagnosed with chronic cystic sinusitis who performed a microbiological examination of the operating material from the sinus. Microflora growth was found in 32 (92.5%), of which 3 cases (3.75%) were yeast - like fungi of the genus Candida, with only 3 (8.5%) patients being dominated by sterile crops, aerobic microorganisms from anaerobics. The result of our studies shows the degree of changes in the normal microbial landscape of the sinuses, and it is recommended to determine the value of the degree of dysbiosis of the paranasal sinuses in order to assess the severity of the pathological process.
Keywords: chronic cystic sinusitis; microbial landscape